Medicinal plants for the treatment and prevention of post-menopausal obesity: a review - Liu, Jing; Akter, Reshmi; Rupa, Esrat Jahan; Van-An, Hoang; Li, Jinfeng; Yang, Deok Chun; Yang, Dong Uk; Awais, Muhammad; Kim, Jong-Hoon (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevancePhytoestrogen-rich plants have been used across various traditional medicine systems, such as Ayurveda, Traditional Chinese Medicine, and Indigenous herbal practices, to address menopausal symptoms including metabolic imbalances and weight gain. The historical use of these plants underscores their therapeutic potential in women’s health, providing a foundation for exploring their modern applications as safer alternatives to hormone replacement therapy (HRT) for post-menopausal obesity.Aim of the reviewThis review aims to systematically evaluate the anti-obesity effects of plant-derived phytoestrogens in managing post-menopausal obesity. It seeks to understand and summarize the mechanisms by which phytoestrogens act as estrogen alternatives, focusing on their cellular and molecular effects, and highlighting specific plants with promising therapeutic properties.Materials and methodsA comprehensive literature search was conducted, covering studies on phytoestrogenic plants used in traditional and contemporary practices for managing obesity. The review examines each plant’s taxonomic family, common name, bioactive compounds, and experimental evidence from cellular and animal models that illustrate potential anti-obesity mechanisms relevant to post-menopausal conditions.ResultsThe analysis reveals that phytoestrogens employ diverse mechanisms in mitigating obesity. Some bind directly to estrogen receptors, mimicking estrogenic effects and inducing cellular responses linked to metabolism. Others inhibit adipogenesis (fat cell formation) and lipogenesis (fat storage), while some enhance thermogenesis (heat production) and lipolysis (fat breakdown), effectively counteracting the metabolic shifts associated with menopause. Specific plants, such as soy (Glycine max (L.) Merr.), red clover (Trifolium pratense L.), and basil-clove (Ocimum gratissimum L.), demonstrate unique pathways for influencing fat metabolism, suggesting a multi-faceted approach to post-menopausal obesity.ConclusionPlant-derived phytoestrogens have been proposed as a potential alternative to HRT for managing post-menopausal obesity. Drawing from both traditional ethnobotanical knowledge and emerging scientific evidence, these compounds may offer a naturally derived strategy that could carry fewer adverse effects. Nevertheless, current findings are preliminary, and more rigorous, large-scale clinical studies are necessary to better understand their efficacy, determine appropriate dosing, and assess possible interactions with conventional therapies.